Cost of hospitalization for firearm injuries by firearm type, intent, and payer in the United States - Corinne Peek-Asa; Brandon Butcher; Joseph E. Cavanaugh (BMC, 2017)
Abstract Background Firearm injuries disproportionately affect young, male, non-White populations, causing substantial individual and societal burden. Annual costs for hospitalized firearm injuries have not been widely described, as most previous cost studies have focused on lifetime costs. We examined a nationally-representative database of hospitalizations in the US to estimate per-hospital and overall hospital costs for firearm injuries by intent, type of weapon, and payer source. Methods We conducted a retrospective cohort study of all firearm injury hospitalizations in the National Inpatient Sample from 2003 through 2013. The National Inpatient Sample, maintained by the Healthcare Utilization Project, is a stratified and weighted national sample of more than 20% of all hospitals. All admissions for firearm injuries were identified through Ecodes, yielding a weighted total of 336,785 for the study period. Average annual per-patient and overall hospital costs were estimated using generalized linear modelling, controlling for patient and hospital variables. Costs by intent, firearm type, and payer sources were estimated. Results Annually from 2003 through 2013, 30,617 hospital admissions were for firearm injuries, for an annual rate of 10.1 admissions per 100,000 US population. More than 80% of hospitalizations were among individuals aged 15-44, and rates were nine times higher for males than females and nearly ten times higher for the Black than the White population. More than 60% of admissions were for assaults, and 70% of the injuries that had a known firearm type were from handguns. The average annual admission cost was $622 million. The highest per-admission costs were for injuries from assault weapons ($32,237 per admission) and for legal intervention ($33,462 per admission), but the highest total costs were for unspecific firearm type ($373 million) and assaults ($389 million). A quarter of firearm injury hospitalizations were among the uninsured, yielding average annual total costs of $155 million. Conclusion Hospitals can project that government insurance will be the highest source for firearm injury reimbursement, and depending on healthcare access laws, that many of their firearm injury admissions will not be covered by insurance.